AN ANALYSIS OF THE TIPOLOGI OF POVERTY GAP INDEX AND POVERTY SEVERITY INDEX BY HDI AND RATE OF GDRP PERCAPITA IN WEST KALIMANTAN 2010-2013 - B01111068, Willhelmina Sari (Jurnal Pembangunan dan Pemerataan, 2016)
This research aimed (1) to analyze the typology of the poverty gap and severity index by the rate of GDRP per capita, (2) to analyze the typology of the poverty gap and severity index by the Human Development Index (HDI), (3) to analyze the typology of HDI by the rate of GDRP per capita.The method used in this research was a descriptive analysis. This research analyzed the typology of regions with the Cartesian diagram. The data used were secondary data obtained from the Central Agency of Statistics. After the data were collected, they were processed using the SPSS.Based on analysis of the typology of the regions, it can be concluded that: (1) most Regencies/Cities were regions which had a high poverty gap index with a low GDRP per capita i.e. 6 Regencies/Cities, while the least were regions which had a high poverty gap and severity index with high GDP per capita i.e. 1 Regency/City respectively. (2) Most Regencies/Cities were regions which had a low poverty severity index with a high rate of HDI i.e. 6 Regencies/Cities, while the least were regions which had a high poverty severity index with a high rate of HDI i.e 2 Regencies/Cities. (3) most Regencies/Cities were relatively underdeveloped regions, either in terms of income and human development i.e. 5 Regencies/Cities, the least were regions which had high GDRP per capita with low HDI i.e. 2 Regencies/Cities.Keyword: Poverty Gap Index (P1), Poverty Severity Index (P2), Poverty, Human Development Index (HDI), GDRP.